Review of "Substance Abuse in Canada" - Block, Aaron L. (Canadian Journal of Counselling and Psychotherapy, 2010)
This book was written for those who have been impacted directly or indirectly by addiction. Myths and assumptions from personal experience and the media are challenged. Tobacco, nicotine, and illicit drugs such as opioids and cannabis are explored in terms of assessment and evidence-based treatment, and from cultural and legal perspectives. Personal choice is compared and contrasted within a biopsychosocial framework when discussing policy development at the federal and provincial level. Canada’s drug policy and evolution is detailed and addiction is firmly placed within a Canadian and international context.